2021
DOI: 10.3390/polym13111828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Composition Effects on the Physicochemical and Biological Properties of Polypeptide-Based Hydrogels for Potential Application in Wound Healing

Abstract: In this study, the effect of crosslinking and concentration on the properties of a new library of low-concentration poly(Lys60-ran-Ala40)-based hydrogels for potential application in wound healing was investigated in order to correlate the hydrogel composition with the desired physicochemical and biofunctional properties to expand the assortment of poly-l-lysine (PLL)-based hydrogels suitable for wound healing. Controlled ring-opening polymerization (ROP) and precise hydrogel compositions were used to customiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…The cross-linker used did not exhibit any toxicity to fibroblasts, endothelial cells or to keratinocytes when compared to standard 2D tissue culture controls. Consistent with our study, collagen cross-linking with 4-arm PEG succinimidyl glutarate did not affect dermal fibroblast viability [26,27]. Our results suggested that the composed hydrogel is biocompatible with living cells and suitable for further in vivo examination.…”
Section: Discussionsupporting
confidence: 91%
“…The cross-linker used did not exhibit any toxicity to fibroblasts, endothelial cells or to keratinocytes when compared to standard 2D tissue culture controls. Consistent with our study, collagen cross-linking with 4-arm PEG succinimidyl glutarate did not affect dermal fibroblast viability [26,27]. Our results suggested that the composed hydrogel is biocompatible with living cells and suitable for further in vivo examination.…”
Section: Discussionsupporting
confidence: 91%
“…As discussed in a study by Giliomee et al , the equilibrium swelling ratio (ESR) is closely related to the network structure of hydrogels. The ESR of the composite microgel scaffolds followed the same trend as the pore sizes.…”
Section: Resultsmentioning
confidence: 99%
“…"Partially Cross-Linked" Inks. The cross-linking between P(KA) and 4-PEG-SG was well-studied in Giliomee et al, 25 and the phase plot was employed to identify soft pliable gels. For the partially cross-linked inks, the soft gel with a concentration of 2 wt % and a 4:1 molar ratio was selected for further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations